Ektopik Gigi 18 Simtomatik pada Sinus Maksilaris: Laporan Kasus - Istadi, Didit; Trihandoko, Feri (e-GiGi, 2025)
Abstract: Ectopic tooth locations outside the normal jaw arch such as on the maxillary sinus are rare. The presence of ectopic signs is often found accidentally by dentists during oral cavity examinations. This is due to the absence of symptoms or complaints in the early days. An understanding of the complications that may occur due to ectopic teeth is very necessary for dentists in providing oral health education. We reported a 26-year-old woman complaining of swelling in her right cheek which had become increasingly painful one week before the examination. Orthopantomograph (OPG) x-ray showed that the right upper third molar was positioned on the right maxillary sinus. A CT scan was carried out to determine the position and boundaries of the third molar teeth. Surgery was performed to remove the upper right third molar tooth under general anesthesia using the Caldwell-Luc approach. The final control results showed significantly reduced pain and swelling. In conclusion, surgical excision using the Caldwell-Luc approach for an ectopic tooth into the maxillary anthrum with symptoms shows good results without significant complaints after the procedure. Good wound healing is observed in the 2nd and 3rd months after surgery. Keywords: ectopic tooth; complications; upper third molar; maxillary sinus    Abstrak: Lokasi gigi ektopik di luar lengkung rahang normal seperti pada sinus maksilaris merupakan kasus jarang. Adanya tanda-tanda ektopik sering kali ditemukan tidak sengaja oleh dokter gigi saat pemeriksaan rongga mulut. Hal ini disebabkan tidak adanya gejala ataupun keluhan pada masa-masa awal. Pemahaman tentang komplikasi yang mungkin terjadi akibat gigi ektopik sangat perlu bagi dokter gigi dalam memberi edukasi kesehatan mulut. Kami melaporkan seorang perempuan berusia 26 tahun, dengan keluhan bengkak di pipi kanan yang bertambah nyeri sejak satu minggu sebelum diperiksa. Rontgen ortopantomograf (OPG) menunjukkan gigi molar ketiga atas kanan posisi berada pada sinus maksilaris kanan. Selanjutnya dilakukan CT-scan untuk menentukan posisi dan batas-batas gigi molar ketiga tersebut. Pembedahan dilakukan untuk mengambil gigi molar ketiga kanan atas, di bawah pengaruh bius total, dengan pendekatan Caldwell-Luc. Hasil kontrol akhir menunjukkan nyeri dan bengkak berkurang secara signifikan. Simpulan laporan kasus ini ialah tindakan eksisi bedah dengan pendekatan Caldwell-Luc pada kondisi gigi ektopik ke dalam antrum maksilaris dengan gejala menunjukkan hasil yang baik dan tidak disertai keluhan berarti setelah tindakan, dengan hasil penyembuhan luka yang baik pada bulan ke-2 dan 3 pasca operasi. Kata kunci: gigi ektopik; komplikasi; molar ketiga atas; sinus maksilaris